2021
DOI: 10.1021/acsaem.1c01133
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Alkaline Zinc/Copper Oxide Batteries

Abstract: Resurrecting a battery chemistry thought to be only primary, we demonstrate the first example of a rechargeable alkaline zinc/copper oxide battery. With the incorporation of a Bi2O3 additive to stabilize the copper oxide-based conversion cathode, Zn/(CuO–Bi2O3) cells are capable of cycling over 100 times at >124 W h/L, with capacities from 674 mA h/g (cycle 1) to 362 mA h/g (cycle 150). The crucial role of Bi2O3 in facilitating the electrochemical reversibility of Cu2O, Cu­(OH)2, and Cuo was supported by scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
(72 reference statements)
0
17
0
Order By: Relevance
“…[ 13 ] The concentric diffraction rings (the inset in Figure 1c) showed that HCONC has polycrystalline characteristics, and the corresponding diffraction ring indices were marked. [ 14 ] In addition, a carbon layer with a thickness of 1.88 nm was observed on the surface of Cu 2 O nanocrystals, which improved the dispersity of HCONC in aqueous solution. The chemical composition and element mapping of HCONC were obtained from high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM).…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] The concentric diffraction rings (the inset in Figure 1c) showed that HCONC has polycrystalline characteristics, and the corresponding diffraction ring indices were marked. [ 14 ] In addition, a carbon layer with a thickness of 1.88 nm was observed on the surface of Cu 2 O nanocrystals, which improved the dispersity of HCONC in aqueous solution. The chemical composition and element mapping of HCONC were obtained from high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM).…”
Section: Resultsmentioning
confidence: 99%
“…. While standalone CuO proved to be a nonideal cathode material, 5 this work and a new study on carbon coated Cu o /Bi o (Figures S3 and S4) show that morphology and additives play a decisive role in the 2− is expected to be similarly critical for extending the cycle life of Zn||CuO batteries, Figure 1c.…”
Section: Azbsmentioning
confidence: 73%
“…Schematic of (c) CuO||Bi 2 O 3 cathode transformation and (d) corresponding cycle performances of Zn||(CuO/Bi 2 O 3 ) AZB. Reproduced with permissions from ref . Copyright 2021 The Authors.…”
Section: Cathode Design and Mechanism Issuesmentioning
confidence: 99%
“…5A), which is 41 V higher than that of their liquid counterparts. [28][29][30][31] We then manufactured a prototype version of the new high voltage membrane-less Zn|MnO 2 , shown in Fig. 5B.…”
Section: Gelled Membrane-less High Voltage Zn|mno 2 Batteriesmentioning
confidence: 99%